Spontaneous splenic rupture: an unusual presentation of CML. (24th March 2011) - Jafferbhoy, Sadaf; Chantry, Andrew; Atkey, Neil; Turner, Douglas; Wyld, Lynda
Abstract : A 47-year-old man presented with sudden onset of severe, generalised abdominal pain and collapse. He also had a 4-month history of lethargy and weight loss. On examination he was shocked with a distended tender abdomen. He had haemoglobin of 3.8 g/dl and a white cell count count of 280.3×10 9 /l with predominance of neutrophils. Arterial gases showed mixed metabolic-respiratory acidosis. A CT scan of abdomen showed active extravasation in splenic bed. In view of probable hyperviscosity syndrome, it was decided to attempt an angiographic embolisation. This was successfully carried out but 4 h later, he developed abdominal compartment syndrome and underwent a laparotomy and splenectomy. Subsequently, bone marrow aspirates were taken which showed granulocytic hyperplasia. Cytogenetic studies confirmed the presence of Philadelphia Chromosome and he was started on Imatinib. It is now 5 months since diagnosis and he has achieved complete haematological and cytogenetic response.